STUDI KASUS TERAPI MUSIK KLASIK DAN AROMATERAPI MAWAR TERHADAP PENURUNAN TEKANAN DARAH PADA PASIEN STROKE NON HEMORAGIK DI RSUD AJI MUHAMMAD PARIKESIT - Artha Yuda, rifkal; Khoiroh Muflihatin, Siti; Marsan Dirdjo, Maridi; Septiawan, Taufik (Alauddin Scientific Journal of Nursing, 2023)
Background: Stroke is a condition in which brain tissue is damaged due to decreased or cessation of oxygen intake in the blood so that cells will die and then no longer function. Non hemorrhagic stroke occurs due to a blockage of blood vessels so that oxygen perfusion to the brain will decrease. One of the causes of stroke is uncontrolled hypertension. Purpose This study aims to determine the effect of classical music therapy and rose aromatherapy on reducing blood pressure in non-hemorrhagic stroke patients. Method: this research method is a One-Shot Case Study. The characteristics of the patients who were respondents were subjects with a medical diagnosis of non-hemorrhagic stroke who had high blood pressure. Implementation results given with innovative classical music therapy and rose aromatherapy, obtained a decrease in blood pressure before and after administration of therapy for 3 days for 15 minutes. The conclusion from the analysis results showed that there was a change in blood pressure after being given the intervention of classical music therapy and rose aromatherapy in non-hemorrhagic stroke patients in the Intermediate room of Aji Muhammad Parikesit Hospital. Recommendation: Application of classical music therapy and rose aromatherapy as a nursing combination therapy that can be used in the management of lowering blood pressure in non-hemorrhagic stroke patients. Keywords: classical music therapy, rose aromatherapy, stroke non hemorrhagic